Pro Windows 8 Development with HTML5 and JavaScript - Freeman, Adam.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Apps are at the heart of Windows 8, bringing rich and engaging experiences to both tablet and desktop users. Windows 8 uses the Windows Runtime (WinRT), a complete reimagining of Windows development that supports multiple programming languages and is built on HTML5, CSS and JavaScript. These applications are the future of Windows development and JavaScript is perfect language to take advantage of this exciting and flexible environment. Seasoned author Adam Freeman explains how to get the most from WinRT and Windows 8 by focusing on the features you need for your project. He starts with the nuts-and-bolts and shows you everything through to advanced features, going in-depth to give you the knowledge you need. Each topic is covered clearly and concisely and is packed with the details you need to learn to be truly effective. The most important features are given a no-nonsense in-depth treatment and chapters contain examples that demonstrate both the power and the subtlety of Windows 8, Windows Runtime and Javascript.
Keywords: Computer science; Computer Science; Computer Science, general